Clinical and Epidemiological Investigation of TCM Syndromes of Patients with Coronary Heart Disease in China - Ren, Yi (Hindawi Publishing Corporation, 2012)
To compare the regional differences in TCM syndromes of patients with coronary heart disease (CHD) between North and South China. A total of 624 patients with a diagnosis of CHD, confirmed by coronary angiography, were included in the comparative analysis to determine the occurrence pattern, characteristics of TCM syndrome distribution, and differences in syndrome combinations and major syndrome types (deficiency or excess) between North and South China. The incidence of CHD tended to be higher in North China (54.6%) compared with that in South China (45.4%). The proportions of patients with a qi-deficiency syndrome (83.7%), turbid phlegm syndrome (68.9%), or blood stasis syndrome (91.5%) were generally higher in the South group, while the proportion of patients with a cold congelation syndrome (7.9%) was identified to be obviously higher in the North group (P < 0.01). Moreover, compared with that in the South group, the overall frequency of syndrome combinations tended to be lower in the North group (P < 0.01); and the most common types of TCM syndrome were excess syndrome (193, 56.6%) and primary deficiency and secondary excess syndrome (244, 86.2%) in the North and South groups, respectively (P < 0.01). A regional difference does exist in the TCM syndromes of patients with CHD between North and South China, indicating that the prevention and treatment of CHD in South China should not only focus on promoting blood circulation and removing blood stasis, but also include supplementing qi and eliminating phlegm